Analisis Strategi Digital Branding Dalam Konten Media Sosial Terhadap Peningkatan Dampak Dan Jangkauan Pada Badan Pusat Statistik Kota Palu - Fajar Surya Alamsyah; Maskuri Sutomo; Zakiyah Zahara; Muh. Riswandi Palawa (Cattleya Darmaya Fortuna, 2024)
This research aims to analyze digital branding strategies in the social media content of the Palu City Central Statistics Agency (BPS) and its impact on increasing public reach and interaction. The research method used is qualitative with a descriptive approach with data collection techniques through observation, in-depth interviews, and analysis of BPS Palu City social media content. Apart from using the method above, the researcher used library research and field research to complete this paper, so that it can be justified theoretically. There were 5 informants for this research. The research results show that an effective digital branding strategy includes the use of attractive visuals, consistency in message delivery, and active engagement with the audience. The increase in public reach and interaction can be seen from the increasing number of followers, likes, comments and shares on BPS Palu City social media content. This research concludes that a planned and targeted digital branding strategy can increase public awareness of the statistical information provided by BPS, as well as expand the reach of this information to the wider community.